Analisis terhadap Karakteristik Maudhu’i dalam Penafsiran Hassan Hanafi - Maulana Yusuf; Sonny Permana (UIN Sunan Gunung Djati Bandung, 2021)
Ideally, an interpretation that uses the tahlili method in classical interpretation is comprehensive and can produce human problems. But in fact, the interpretation of this model does not touch human issues. Instead, it tends to be rigid and very fixated on the text. This study aims to determine the maudhu'i (thematic) method of Hassan Hanafi in his work al-Din wa al-Tsaurah. This study seeks to answer the orientation of the interpretation of the al-Qur'an Hassan Hanafi towards the people's revolutionary movement. By using the content analysis method, namely by analyzing and processing messages or a tool to observe and analyze the content of open communication behavior of the selected research object. The results showed that the characteristics of Hassan Hanafi's maudhu'i method could include the following: first, Hassan Hanafi's thematic interpretation was juz'iyyah (specific) not kuliyah (comprehensive); secondly, Hassan Hanafi's thematic interpretation is thematic, which more analyzes on certain themes which are closely related to humanity; third, Hassan Hanafi's thematic interpretation is temporal; fourth, Hassan Hanafi's thematic interpretation is realistic; Hassan Hanafi's five thematic interpretations are oriented towards specific meanings and not just rhetoric about letters and words; sixth, thematic experimental interpretation; seventh, thematic interpretations that pay attention to contemporary problems, eighth, this shows that the interpreter's social position has changed the pattern of interpretation.